(untitled) (International Journal of Built Environment and Sustainability, 2025)
Considering the critical importance of public transportation, especially rail transit, in shaping urban landscapes and its alignment with the United Nations Sustainable Development Goals, this investigation delves into the architectural intricacies of rail transit environments through the lens of inclusivity. This scholarly inquiry adopts a multifaceted qualitative research methodology that synergizes empirical case studies, the formulation of strategic frameworks, and the application of design methodologies to elucidate and operationalize the principles of inclusive design within the context of rail transit systems.The study embarked on an initial empirical exploration through an in-depth case study of Singapore’s Thomson-East Coast Line, where able-bodied participants role-played and engaged in an immersive experience by wearing glasses that simulate mild visual impairment. By coding the data from these on-site experiences, a robust inclusive design framework was distilled, characterized by a tripartite structural hierarchy and four thematic pillars. Building on this foundational framework, the study proposed a quintet of innovative inclusive design prototypes tailored to enhance the tactile interaction points within rail transit environments. These prototypes were further evaluated through the reconstruction of subway navigation scenarios experienced by visually impaired commuters, employing storyboards as a tool for situational analysis. The comprehensive inclusive design framework and the ensuing design prototypes unveiled through this study hold profound implications for the strategic planning and architectural design of urban rail transit systems, particularly within the ambit of nascent urban centers poised to embark on or currently engaged in the development of rail transit infrastructures. This research significantly contributes to the discourse on sustainable urban development and the promotion of social inclusiveness, presenting actionable insights for policymakers, urban planners, and designers engaged in the creation of more accessible and inclusive urban transit ecosystems.